Quantitative Analysis and Carbon Reduction Strategies Based on Spatiotemporal Electricity Carbon Emission Factors - Tian, Zhuang; Gao, Yi; Wu, Jiaowen; Tang, Yachen; Liu, Guangyi; Yun, Jiangyang (International Journal of Sustainable Energy Planning and Management, 2025)
Different temporal and spatial dimensions of carbon accounting can yield varying carbon emission results. Fine-grained time- and region-specific carbon emission factor accounting for a target power grid can improve both accuracy and interpretability. This paper used a central China power grid as a case study to examine the calculation methods for carbon emission factors across different temporal and spatial dimensions. It focused on the differences in carbon accounting at substation, administrative, and voltage levels across various time periods. First, the paper summarized the development trends in power grid carbon emission factor calculations, highlighting the importance of regional division and time-based accounting. Second, a multidimensional carbon emission factor calculation method was proposed based on the coupling mechanism between power generation and carbon emissions, emphasizing the close relationship between carbon emissions and electricity under different generation structures and energy usage patterns. Finally, through quantitative analysis, the paper examined carbon emission variations across different temporal and spatial ranges and discussed the advantages and disadvantages of various partitioning strategies from the perspectives of power generation companies, electricity consumers, and the government. The study provides valuable insights for further research and standardization of carbon emission factors in power grids.